BERMAIN KOTAK BENTUK GEOMETRI TERHADAP HASIL BELAJAR MATEMATIKA BANGUN DATAR ANAK AUTIS - S, MUZAYYINATUS (Jurnal Pendidikan Khusus, 2016)
Abstract   The research of the influence of playing a box of geometry form toward the result of learning mathematics of flat structure to autism children in SLB Cita Hati Bunda Sidoarjo was formed background by the autism children’s ability in recognizing and grouping the form of flat structure (triangle, rectangle, and around) which still needed to be developed so the researcher gave fun activity which could facility the autism children to understand the flat structure material through the activity of playing a box of geometry form. The activity of learning mathematics of flat structure was not applied yet before in SLB Cita Hati Bunda Sidoarjo. The purpose of this research was to prove whether there was influence of playing a box of geometry form toward the result of learning mathematics of flat structure to autism children in SLB Cita Hati Bunda Sidoarjo. The research method used was quantitative approach with pre experiment kind and one group pretest posttest design. The sampling technique used was purposive sample and the technique of data collection was test. There were two tests done i.e. the test was done to assess the children’s initial ability before and after giving treatment of playing a box of geometry form. The technique of data analysis used statistic non parametric, the test was done by Wilcoxon Match Pair Test formula. The research result indicated that the test average value obtained before giving treatment of playing a box was 37,28 while the test average value obtained after giving treatment of playing a box of geometry form was 75,27, it indicated that there was enhancement value. In addition, the research result also indicated Tcounted = 0 was smaller than Ttable = 2 with significant level 5%. If Tcounted = 0 < Ttable = 2 so it could be concluded that there was influence of playing a box of geometry form toward the result of learning mathematic of flat structure to autism children in SLB Cita Hati Bunda Sidoarjo.   Keywords: playing,  a box of geometry form